UMUMIY O‘RTA TA’LIM MAKTAB O‘QUVCHILARI KIMYO FANINI O‘ZLASHTIRISHIDAGI MUAMMOLARNI BARTARAF ETILISHI - Ismailov , Saidjon (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
the general education school presents ideas about problems and solutions in the development of chemistry by students, pedagogical technologies in teaching subjects related to chemistry.